Three-phase current-source shunt active power filter with solar photovoltaic grid interface - Exposto, Bruno Fernandes (2015)
This paper presents the proposal of a three phase current source shunt active power filter (CS-SAPF) with photovoltaic grid interface. The proposed system combines the compensation of reactive power and harmonics with the injection of energy from a solar photovoltaic array into the electrical power grid. The proposed equipment presents the advantage of giving good use to the current source inverter, even when the solar photovoltaic array is not producing energy. The paper describes the control system of the CS SAPF, the energy injection control strategy, and the current harmonics and power factor compensation strategy. Simulation results to assess the performance of the proposed system are also presented.